The work of the foreigner in Iraq (Journal of the College of Basic Education, 2022)
The importance of the topic and the motive for its research:The issue of foreign labor is currently of great importance in all countries for some reasonsuffering from the problem of unemployment; Hence, the interest of those countries in this issue stems in part from necessityProtecting the national workforce from the danger of competing with the foreign workforce, as the other side liesIn self-sufficiency and rehabilitation of national manpower; And even the states that do not suffer from this problem and we meanIn the countries that receive foreign workers, we see that they do not neglect this issue, and that is aware of themThe necessity of its labor market and taking into account the control of the social and economic aspect on which it dependsThe phenomenon of emigration in order to work in those countries.